Hubungan Kualitas Air terhadap Pertumbuhan Udang Vaname (Litopenaeus Vannamei) di PT Alam Lepar Sejahtera Bangka Belitung - Baiq Melly Rafika Wathoni; Didik Budiyanto; Muhajir Muhajir (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This study aims to analyze the effect of the Human Development Index (HDI), economic growth, and the open unemployment rate on poverty levels in Tuban Regency during the period 2010–2024. This research uses a quantitative approach with multiple linear regression analysis and secondary data obtained from the Central Statistics Agency and other relevant institutions. The results indicate that HDI has a negative and significant effect on poverty, demonstrating that improvements in education, health, and living standards contribute significantly to poverty reduction. Meanwhile, economic growth and the open unemployment rate show positive but insignificant effects on poverty levels. These findings indicate that economic growth has not been optimally distributed among communities, while the dominance of the informal sector in the labor structure causes unemployment to have limited direct influence on poverty conditions. Simultaneously, HDI, economic growth, and the open unemployment rate significantly affect poverty levels in Tuban Regency. Therefore, effective policies emphasizing human resource development, employment improvement, and inclusive economic growth are required to accelerate poverty alleviation. This study provides important insights for local governments in formulating sustainable development strategies to reduce poverty through improving community welfare and economic equality.